Reovirus infection and tissue injury in the mouse central nervous system are associated with apoptosis. - Oberhaus, S M (1997)
Reovirus serotype 3 strains infect neurons within specific regions of the neonatal mouse brain and produce a lethal meningoencephalitis. Viral replication and pathology colocalize and have a predilection for the cortex, hippocampus, and thalamus. We have shown previously that infection of cultured fibroblasts and epithelial cells with reovirus type 3 Dearing (T3D) and other type 3 reovirus strains results in apoptotic cell death, suggesting that apoptosis is a mechanism of cell death in vivo. We now report that T3D induces apoptosis in infected mouse brain tissue. To determine whether reovirus induces apoptosis in neural tissues, newborn mice were inoculated intracerebrally with T3D, and at various times after inoculation, brain tissue was assayed for viral antigen by immunostaining and apoptosis was identified by DNA oligonucleosomal laddering and in situ terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling. Cells were also stained with cresyl violet to detect morphological changes characteristic of apoptosis, including chromatin condensation and cell shrinkage. DNA laddering was detected in T3D- but not in mock-infected brain tissue. Apoptotic cells were restricted to the same regions of the brain in which infected cells and tissue damage were observed. These findings suggest that virus-induced apoptosis is a mechanism of cell death, tissue injury, and mortality in reovirus-infected mice. The correlation between apoptosis and pathogenesis in vivo identifies apoptosis as a potential target for molecular and pharmacological strategies designed to curtail or prevent diseases resulting from induction of this cell death pathway.